High-flux laser additive manufacturing method for nickel-titanium alloy
By adopting high-throughput selected laser melting technology and remelting process in laser additive manufacturing of nickel-titanium alloys, the process parameters and the laser power are optimized, and the cracking and unsolved particle defects in the manufacturing process of nickel-titanium alloys are solved, and the preparation of nickel-titanium alloys with dense structure and high shape memory effects is achieved.
Patent Information
- Application Number
- CN202411955946.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has defects such as cracking and unsolved particles in the laser additive manufacturing process of nickel-titanium shape memory alloys, resulting in the formation and expansion of cracks in the tissue.
Using high-throughput selected laser melting technology and remelting process, Ni-titanium alloy is deposited layer by layer by layer by layer by optimizing process parameters and reducing laser power.
It effectively avoids cracking and unsolved particle defects in the laser additive manufacturing process, reduces the formation and expansion of cracks in the tissue, and improves the metallurgical quality and shape memory effect of the nickel-titanium alloy.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal parts manufacturing, and in particular to a high-throughput laser additive manufacturing method for nickel-titanium alloy. Background Art
[0002] At present, shape memory alloys (SMA) are a class of metal materials with special physical and mechanical properties, the most common representative of which is nickel-titanium alloy (NiTi). In addition, there are other alloys such as copper-zinc-aluminum alloy and iron-manganese alloy. This material can automatically return to a preset shape after being heated to a specific temperature, showing a unique shape memory effect. In addition, shape memory alloys also have superelastic properties and can maintain high resilience under large deformation, which makes them very popular in engineering applications. However, traditional SMA manufacturing methods such as smelting, casting and powder metallurgy have limitations, such as high cost, long cycle, and limited shape complexity. Laser additive manufacturing technology manufactures parts of complex shapes by adding materials layer by layer. Laser additive manufacturing can achieve highly complex designs, and has advantages in material utilization and production efficiency. Defects can be eliminated through the remelting process, and finally a well-formed shape memory alloy can be prepared.
[0003] Nickel-titanium shape memory alloy (NiTi) is widely used in aerospace, medical devices, robotics and smart materials due to its unique shape memory effect and superelastic properties. Shape memory alloy can return to a preset shape at a specific temperature, making it have great application potential in dynamic and complex environments.
[0004] At present, it has been proposed to use pure Ni and Ti element powders to mix for additive manufacturing to synthesize NiTi alloy in situ. This method can more easily and flexibly control the Ni / Ti ratio of the target alloy. Some studies have achieved the manufacture of mixed powder nickel-rich NiTi alloy by laser additive manufacturing technology by mixing nickel-rich NiTi alloy and pure nickel powder through a ball mill, and then adjusting the process parameters. Although the shape memory alloy formed by laser additive manufacturing of Ni and Ti element powders has great application potential as a new material, its preparation difficulty is much greater than that of laser additive manufacturing of NiTi alloy powder forming nickel-titanium shape memory alloy. Since the melting, solidification and cooling of the material are all carried out under extremely fast conditions, it is easy to produce large thermal stress in the formed part, and Ni and Ti are alloys with large differences in properties. There are huge differences in thermal properties such as melting point and thermal expansion coefficient between the two. The melting behavior of mixed alloy powder in the molten pool is more complicated than that of a single alloy. Previous studies have shown that there are some metallurgical quality problems in the forming process of nickel-titanium shape memory alloy formed by using Ni and Ti element powders as raw materials, among which the most typical metallurgical quality melting unevenness and macro cracking.
[0005] Cracks in laser additive manufacturing are the result of the combined effects of organizational characteristics and material thermophysical properties. Most cracks are solidification cracks and solid-state cracks. Solidification cracks originate from intergranular liquid film cracking under tensile stress. The uneven melting of metallurgical quality is due to the difference in melting points between Ni and Ti that is greater than 400°C. When the two powders enter a molten pool of a certain temperature at the same time, pure Ti powder with a higher melting point is more difficult to melt and is prone to forming unmelted powder defects. Summary of the invention
[0006] In order to solve the above technical problems, the present application provides a high-throughput laser additive manufacturing method for nickel-titanium alloy.
[0007] The present application provides a high-throughput laser additive manufacturing method for nickel-titanium alloy, which specifically comprises the following steps in sequence: Step 1: Using pure Ni powder and pure Ti powder as raw materials, a single layer of alloy is deposited on a substrate using a laser additive manufacturing method as a transition layer; Step 2: Pure Ni powder and pure Ti powder are used as raw materials, respectively put into the powder feeder of the laser additive technology equipment, mixed according to the composition ratio, and the first deposition is performed on the single-layer alloy formed in step 1 by high-throughput selective laser melting technology to form a single-layer solid sheet, and then the same sheet powder is remelted; After remelting, pure Ni powder and pure Ti powder are used as raw materials, and high-throughput selective laser melting technology is used for layer-by-layer deposition to print the macroscopic tensile parts of Ni-Ti dissimilar metal forming parts. Single-layer solid sheets are gradually accumulated to form nickel-titanium alloy, and then the substrate is removed to obtain the finished product; The process parameters of the deposition in step 1 and the first deposition in step 2 are: laser power 235-245 W, scanning speed 500-550 mm / s, scanning spacing 130-150 μm, and layer thickness 30-40 μm; The remelting process is as follows: when repeatedly depositing the same layer of powder, the laser power is reduced compared to the process parameters of the first deposition, while other process parameters remain unchanged.
[0008] The technical problem to be solved by this application is to provide a laser additive manufacturing method for Ni-Ti dissimilar metal parts in view of the deficiencies of the prior art. This method avoids defects such as cracking and undissolved particles in Ni-Ti gradient materials during laser additive manufacturing by optimizing the manufacturing process and remelting process, thereby reducing the formation and expansion of cracks in the structure of Ni-Ti dissimilar metal parts. The obtained Ni-Ti dissimilar metal parts have dense structure, small transition zone volume, shape memory effect, and a wide range of applications.
[0009] This application uses pure Ni powder and pure Ti powder as raw materials and mixes them according to the proportion of ingredients through the pneumatic powder mixer of the equipment. Through the observation of the microstructure of the formed part, it is found that: according to the results of EPMA, the micromorphology of the cracks in the sample is found to show no exposed dendrites and or liquid phase traces at the grain boundary. The morphology is straighter and cleaner, and is often accompanied by sharp kinks, which is a characteristic of strain failure cracks in solid cracks. The formation of strain aging cracks is closely related to the cyclic heating-cooling effect in the laser additive manufacturing process. Its strain aging cracking sensitivity is relatively higher in the additive manufacturing process, and it is easier to form cracks. A wedge-shaped structure is found in the crack micromorphology, which is a typical feature of high-temperature plastic loss cracks in solid cracks. In addition, a small amount of dendritic structure of solidification cracks is found in the sample. This application uses a remelting process, and as the number of remelting increases, the laser power decreases, which effectively improves the crack defects.
[0010] In the deposition process using high-throughput selective laser melting technology, pure Ni powder and pure Ti powder are mixed in an atomic ratio of 50-53:47-50 through two synchronous powder feeders of the equipment; the preferred powder feeding process is uniform and controllable, the powder flow is symmetrically distributed, and the deposition accuracy is improved.
[0011] Preferably, in step 1, the substrate is a NiTi alloy substrate, which is cleaned with ethanol and air-dried before printing, and then preheated to 180-200°C.
[0012] Preferably, the atomic ratio of the pure Ni powder to the pure Ti powder is 50-53:47-50.
[0013] Preferably, the atomic ratio of the pure Ni powder to the pure Ti powder is 50.5:49.5.
[0014] Preferably, the pure Ni powder is 99.99% pure Ni powder, which is spherical and has a particle size of 15-53 μm; the pure Ti powder is 99.99% pure Ti powder, which is spherical and has a particle size of 15-53 μm; before printing, the pure Ni powder and the pure Ti powder are vacuum dried in a vacuum incubator at 80°C for 5-8 hours.
[0015] The preferred shapes and particle sizes of both pure Ni powder and pure Ti powder meet the requirements of powder feeding laser additive manufacturing, which is beneficial to the forming of Ni-Ti dissimilar metals; at the same time, the iron-nickel alloy powder with the preferred particle size has a larger surface area, which is more conducive to the absorption of heat and is therefore easier to melt, further ensuring the full melting of the high melting point Ti powder in the deposited Ni-Ti and avoiding the phenomenon of unmelted particles in the Ni-Ti formed parts.
[0016] Preferably, the laser additive manufacturing method in step 1 is a laser selective melting method; the deposition process parameters are: laser power 240 W, scanning speed 550 mm / s, scanning spacing 130 μm, and layer thickness 30 μm.
[0017] Preferably, the thickness of the single-layer solid sheet is 30-40 μm, which is conducive to ensuring the dimensional accuracy of Ni-Ti dissimilar metal parts and improving the quality of each Ni-Ti formed part.
[0018] Preferably, the deposition process parameters are: laser power 240 W, scanning speed 550 mm / s, scanning spacing 130 μm, and layer thickness 30 μm.
[0019] Preferably, in step 2, the process parameters of the first deposition are: laser power 235-245W, scanning speed 500-550mm / s, scanning spacing 130-150μm, and layer thickness 30-40μm; the process parameters of the remelting process are: the number of remelting times is 2-4 times; as the number of remelting times increases, the laser power of the laser additive manufacturing method used in the process parameters gradually decreases.
[0020] Preferably, when the number of remelting times is 2 times, the laser power of the second remelting is 60-90% of the laser power parameter of the first time; when the number of remelting times is 3 times, the laser power of the third remelting is 70-90% of the laser power parameter of the second time; when the number of remelting times is 4 times, the laser power of the third remelting is 80-90% of the laser power parameter of the third time.
[0021] In a specific embodiment, when the number of remelting is 2 times, the laser power of the second remelting is 60%, 70%, 80%, and 90% of the laser power parameter of the first remelting.
[0022] Through experiments, it can be known that the above-mentioned remelting process adopted in this application is conducive to enhancing the bonding force between Ni and Ti powders and improving the performance of Ni-Ti dissimilar metal parts. With the increase of the number of remelting times, the laser power of the laser additive manufacturing method used in the process parameters is gradually reduced, while the process parameters such as scanning spacing and scanning speed remain unchanged, which reduces the cracks and unmelted particle defects in the Ni-Ti dissimilar alloy formed parts, and is conducive to exerting the shape and effect of the formed parts.
[0023] Preferably, the deposition process using the laser additive manufacturing method is carried out in a 99.99% argon atmosphere.
[0024] The deposition process using the laser additive manufacturing method is carried out in an argon atmosphere; the argon atmosphere is an inert gas, and the deposition is carried out in an argon atmosphere, which effectively avoids the oxidation of Ni powder and Ti powder in the laser additive manufacturing method, thereby improving the quality of Ni-Ti dissimilar material metal parts.
[0025] On the other hand, the present application provides a nickel-titanium alloy prepared using the above-mentioned manufacturing method.
[0026] In summary, the technical solution of this application has the following effects: The present application avoids defects such as macro cracking, difficult forming and unmelted particles in the manufacturing process of Ni-Ti dissimilar metal parts by optimizing process parameters and adopting remelting process, ensuring that the obtained Ni-Ti dissimilar metal parts have smaller macro defects, dense structure, and shape memory effect, which significantly reduces the production cost and production cycle of nickel-titanium shape memory alloys.
[0027] This application adopts a laser additive manufacturing method. In order to solve the poor fusion phenomenon caused by the large difference in thermal properties between Ni and Ti, the scanning speed is reduced and the remelting process is controlled to avoid defects such as cracking and undissolved particles of Ni-Ti alloy in the laser additive manufacturing process, thereby reducing the formation and expansion of cracks in the structure of Ni-Ti dissimilar metal parts.
[0028] The present application adopts a laser additive manufacturing method to prepare Ni-Ti dissimilar material metal parts. By remelting in the same single-layer entity and reducing the laser power as the number of remelting times increases, while keeping process parameters such as scanning spacing and scanning speed unchanged, the quality of Ni-Ti dissimilar material metal parts is improved, the difference in thermal expansion coefficients between Ni and Ti is reduced, and excessive stress on Ni and Ti caused by rapid heating and cooling during laser additive manufacturing is avoided, thereby reducing the formation and expansion of cracks, improving the connection strength of Ni-Ti dissimilar material metal parts, and alleviating the physical property mismatch phenomenon of Ni-Ti dissimilar material metal parts.
[0029] The Ni-Ti dissimilar metal parts prepared in the present application have dense structure, excellent mechanical properties, shape memory effect, and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a diagram illustrating the technical route of the equipment in which the powder feeder of the high-throughput selective laser melting equipment of the present invention mixes pure Ni powder and pure Ti powder through the pneumatic powder mixer provided by the equipment.
[0031] Figure 2 This is an EDS result diagram of randomly sampled powder after pure Ni powder and pure Ti powder are mixed by the powder feeder of the high-throughput selective laser melting equipment of the present invention through the pneumatic powder mixer provided by the equipment.
[0032] Figure 3(a) is a comparison diagram of a plate material (alloy powder) of a tensile part prepared using NiTi alloy powder as raw material in the prior art and a plate material (element powder) of a Ni-Ti dissimilar metal tensile part prepared using Ni and Ti element powders as raw materials in this embodiment. Figure 3 (b) is a rod-shaped tensile rod of the Ni-Ti dissimilar material prepared in this embodiment for shape memory experiment.
[0033] Figure 4 This is the microstructure diagram of the Ni-Ti dissimilar material metal part prepared in Example 1.
[0034] Figure 5 This is the DSC test result of the Ni-Ti dissimilar metal parts prepared in Example 1.
[0035] Figure 6 This is the microstructure diagram of the Ni-Ti dissimilar metal part prepared in Example 2.
[0036] Figure 7 This is the DSC test result of the Ni-Ti dissimilar metal parts prepared in Example 2.
[0037] Figure 8 For Comparative Example 1 ( Figure 8 a. Figure 8 b) and Comparative Example 2 ( Figure 8 c. Figure 8 d) Microstructure of the prepared Ni-Ti dissimilar metal parts.
[0038] Fig. 9 This is the DSC test result of the Ni-Ti dissimilar metal parts prepared in Comparative Example 1.
[0039] Fig.10 This is the DSC test result of the Ni-Ti dissimilar metal parts prepared in Comparative Example 2. DETAILED DESCRIPTION
[0040] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example Example
[0041] Example 1 provides a nickel-titanium alloy and a high-throughput laser additive manufacturing method thereof.
[0042] The high-throughput laser additive manufacturing method of nickel-titanium alloy in this embodiment is as follows: Step 1: Using pure Ni powder and pure Ti powder as raw materials, a laser additive manufacturing method of high-throughput selective laser melting is used to deposit a single layer of alloy as a transition layer on a NiTi alloy substrate in an argon atmosphere; the pure Ni powder and pure Ti powder are spherical and have a particle size of 15-53 μm. Before printing, the pure Ni powder and pure Ti powder are vacuum dried in a vacuum incubator at 80°C for 6 hours; the NiTi alloy substrate is pre-cleaned with ethanol, air-dried, and preheated to 180°C; the deposition parameters are: laser power 240W, scanning speed 550mm / s, scanning spacing 130μm, layer thickness 30μm, and spot diameter 150μm; Step 2: Accurately weigh the pure Ni powder and pure Ti powder that were vacuum dried in a vacuum incubator at 80°C for 6 hours in step 1, and then place them into a DLM-120HT high-throughput selective laser melting equipment (such as Figure 1 The mass of pure Ni powder and pure Ti powder delivered by powder feeder 1 and powder feeder 2 after 20 turns of powder feeder 1 and powder feeder 2 is measured, and the average value is taken after five measurements. The calibration result is then input into the powder mixing control system, and the pure Ni powder and pure Ti powder are mixed in a ratio of 50.5:49.5 in atomic ratio, and the powder is mixed by the pneumatic powder mixer of the equipment (such as Figure 2 The figure shows the EDS result of the randomly sampled powder after the pure Ni powder and pure Ti powder are mixed by the powder feeder of the high-throughput selective laser melting equipment through the pneumatic powder mixer of the equipment. It can be seen from the figure that the Ni powder and the pure Ti powder are mixed evenly). After the powder mixing process is completed, the equipment automatically starts printing, that is, the selective laser melting technology is used to perform the first deposition on the single-layer alloy formed in step 1 in an argon atmosphere (the deposition parameters are: laser power 240W, scanning speed 550mm / s, scanning spacing 130μm, layer thickness 30μm, spot diameter 150μm), forming a single-layer solid sheet, and then the same sheet powder is remelted; the same sheet powder is remelted twice, and the laser power during remelting is 80% of the first time, while other process parameters such as scanning speed and scanning spacing remain unchanged, and finally a cubic formed part with a thickness of 10mm×10mm×10mm is formed to facilitate microstructure observation and defect analysis; After remelting, pure Ni powder and pure Ti powder are used as raw materials, and high-throughput selective laser melting technology is used to perform layer-by-layer deposition according to the same process parameters and remelting method mentioned above to print Ni-Ti dissimilar metal formed parts in macro-tensile form. Single-layer solid sheets are gradually accumulated to form nickel-titanium alloy, and then the substrate is removed to obtain Ni-Ti dissimilar material metal parts. Finished products.
[0043] Figure 3(a) is a comparison diagram of a plate material (alloy powder) of a tensile part prepared using NiTi alloy powder as raw material in the prior art and a plate material (element powder) of a Ni-Ti dissimilar metal tensile part prepared using Ni and Ti element powders as raw materials in this embodiment. Figure 3 (b) is a rod-shaped tensile rod of the Ni-Ti dissimilar material prepared in this embodiment for shape memory experiment. It can be seen that the finished Ni-Ti dissimilar material metal parts prepared in this embodiment have good overall metallurgical quality and good appearance quality.
[0044] Figure 4 The microstructure diagram of the Ni-Ti dissimilar metal parts prepared in this embodiment is shown in FIG. Figure 4 It can be seen that the nickel-titanium alloy formed parts formed from pure Ni powder and pure Ti powder as raw materials in this embodiment are well fused, there is no cracking inside the prepared Ni-Ti dissimilar material metal parts, no defects such as cracks and undissolved particles are found, the overall metallurgical quality is good, and the cladding quality is good.
[0045] After testing, Figure 5 The DSC test results of the Ni-Ti dissimilar metal parts prepared in this embodiment are shown in Figure 2. f The temperature is 13.05℃, A f The temperature is 99.67°C and has a shape recovery of 2.5%. Example
[0046] Example 2 provides a nickel-titanium alloy and a high-throughput laser additive manufacturing method thereof.
[0047] The difference between this embodiment and embodiment 1 is that when the same sheet powder is remelted twice, the laser power during the second remelting is 60% of the first remelting power. The remaining process parameters in this embodiment are the same as those in embodiment 1.
[0048] Figure 6 This is a microstructure diagram of the Ni-Ti dissimilar material metal part prepared in this embodiment. It can be seen from the figure that there is no cracking phenomenon inside the Ni-Ti dissimilar material metal part prepared in this embodiment, and no defects such as cracks and undissolved particles are found. The overall metallurgical bonding is good and the cladding quality is good.
[0049] After testing, Figure 7 The DSC test results of the Ni-Ti dissimilar metal parts prepared in this embodiment. f The temperature is 21.17℃, A f The temperature is 98.68°C and has a shape recovery of 2.5%.
[0050] This comparative example provides a nickel-titanium alloy and a high-throughput laser additive manufacturing method thereof.
[0051] The difference between this comparative example and Example 1 is that the process parameters of the deposition in step 1 and the first deposition in step 2 are: laser power 255W, scanning speed 600mm / s, scanning spacing 130μm, layer thickness 30μm. The remaining process parameters in this comparative example are the same as those in Example 1.
[0052] Figure 8 ( Figure 8 a. Figure 8 b) is the microstructure diagram of the 10mm×10mm×10mm cubic formed part of the Ni-Ti dissimilar metal part prepared in this comparative example. It can be seen from the figure that there are multiple cracks in the Ni-Ti cladding layer, showing crack kinks ( Figure 8 a) Wedge-shaped structure ( Figure 8 b) The cracks propagate laterally, with the longest crack being 3.5 mm long and extending to the surface of the specimen to become a macro crack, indicating that there is a large internal stress at the interlayer junction, which gradually expands downward along the grain boundary; this indicates that the overall metallurgy and cladding quality of this comparative example are poor.
[0053] After testing, Fig. 9 The DSC test results of the Ni-Ti dissimilar metal parts prepared in this comparative example are shown in Table 2. f The temperature is 17.82℃, A f The temperature was 90.53°C, and the shape memory experiment could not be performed due to poor forming of the macroscopic part.
[0054] This comparative example provides a nickel-titanium alloy and a high-throughput laser additive manufacturing method thereof.
[0055] The difference between this comparative example and Example 1 is that the same sheet powder is not subjected to a remelting process. The remaining process parameters in this comparative example are the same as those in Example 1.
[0056] Figure 8 ( Figure 8 c. Figure 8 d) is the microstructure diagram of the 10mm×10mm×10mm cubic formed part of the Ni-Ti dissimilar metal part prepared in this comparative example. It can be seen from the figure that there are multiple cracks in the Ni-Ti cladding layer, showing solidification cracks ( Figure 8 c) and dendritic structures ( Figure 8 d), crack propagation, the crack width is obviously wider, and it becomes a macro crack on the surface of the sample, indicating that there is a large internal stress at the interlayer junction, which gradually expands downward along the grain boundary; this shows that the overall metallurgy and cladding quality of this comparative example are poor.
[0057] After testing, Fig.10 The DSC test results of the Ni-Ti dissimilar metal parts prepared in this comparative example are shown in Table 2. f The temperature is 21.07℃, A f The temperature was 95.58°C, and the shape memory experiment could not be performed due to poor forming of the macroscopic part.
[0058] By comparing the embodiments of the present application with the comparative examples, it can be seen that the present application adopts a remelting process to form a single-layer powder, which reduces internal stress and allows both pure Ni powder and pure Ti powder in the mixed powder to be fully melted, thereby avoiding defects such as cracking and undissolved particles in Ni-Ti dissimilar material metal parts during the laser additive manufacturing process, thereby reducing the formation and expansion of cracks in the structure of Ni-Ti dissimilar material metal parts.
[0059] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A high-throughput laser additive manufacturing method for nickel-titanium alloy, characterized in that: Specifically, the following steps are performed in sequence: Step 1: Using pure Ni powder and pure Ti powder as raw materials, a single layer of alloy is deposited on a substrate using a laser additive manufacturing method as a transition layer; Step 2: Pure Ni powder and pure Ti powder are used as raw materials, respectively put into the powder feeder of the laser additive technology equipment, mixed according to the composition ratio, and the first deposition is performed on the single-layer alloy formed in step 1 by high-throughput selective laser melting technology to form a single-layer solid sheet, and then the same sheet powder is remelted; After remelting, pure Ni powder and pure Ti powder are used as raw materials, and high-throughput selective laser melting technology is used for layer-by-layer deposition to print the macroscopic tensile parts of Ni-Ti dissimilar metal forming parts. Single-layer solid sheets are gradually accumulated to form nickel-titanium alloy, and then the substrate is removed to obtain the finished product; The process parameters of the deposition in step 1 and the first deposition in step 2 are: laser power 235-245 W, scanning speed 500-550 mm / s, scanning spacing 130-150 μm, and layer thickness 30-40 μm; The remelting process is as follows: when repeatedly depositing the same layer of powder, the laser power is reduced compared to the process parameters of the first deposition, while other process parameters remain unchanged.
2. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 1, characterized in that: In step 1, the substrate is a NiTi alloy substrate, which is cleaned with ethanol and air-dried before printing, and then preheated to 180-200°C.
3. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 1, characterized in that: The atomic ratio of the pure Ni powder to the pure Ti powder is 50-53:47-50.
4. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 3, characterized in that: The atomic ratio of the pure Ni powder to the pure Ti powder is 50.5:49.
5.
5. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 1, characterized in that: The model of the pure Ni powder is pure Ni powder with a content of 99.99%, the pure Ni powder is spherical and the particle size is 15-53 μm; the model of the pure Ti powder is pure Ti powder with a content of 99.99%, the pure Ni powder is spherical and the particle size is 15-53 μm; before printing, the pure Ni powder and the pure Ti powder are vacuum dried in a vacuum insulation box at 80° C. for 5-8 hours.
6. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 5, characterized in that: Step 1: The laser additive manufacturing method is a laser selective melting method; the deposition process parameters are: laser power 240W, scanning speed 550mm / s, scanning spacing 130μm, and layer thickness 30μm.
7. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 1, characterized in that: In step 2, the process parameters of the remelting process are: the number of remelting times is 2-4 times; as the number of remelting times increases, the laser power of the laser additive manufacturing method used in the process parameters gradually decreases.
8. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 7, characterized in that: When the remelting number is 2 times, the laser power of the second remelting is 60-90% of the laser power parameter of the first time; when the remelting number is 3 times, the laser power of the third remelting is 70-90% of the laser power parameter of the second time; when the remelting number is 4 times, the laser power of the third remelting is 80-90% of the laser power parameter of the third time.
9. The high-throughput laser additive manufacturing method of nickel-titanium alloy according to claim 1, characterized in that: The deposition process using the laser additive manufacturing method is carried out in a 99.99% argon atmosphere.
10. A nickel-titanium alloy, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for optimizing nickel-titanium alloy performance based on selective laser melting method
CN115703153A
Uniform forming additive manufacturing method based on SLM
CN117862529A
Selective laser melting heterogeneous metal same-layer forming method
CN119057078A
Method for additive manufacturing of three-dimensional objects from metallic glasses
US20190001440A1
Powder bed fusion additive manufacturing methods and apparatus
US20230356301A1